Early postnatal administration of an AAV9 gene therapy is safe and efficacious in CLN3 disease - Johnson, Tyler B.; Brudvig, Jon J.; Likhite, Shibi; Pratt, Melissa A.; White, Katherine A.; Cain, Jacob T.; Booth, Clarissa D.; Timm, Derek J.; Davis, Samantha S.; Meyerink, Brandon; Pineda, Ricardo; Dennys-Rivers, Cassandra; et al. (Frontiers in Genetics, 2023)
CLN3 disease, caused by biallelic mutations in the CLN3 gene, is a rare pediatric neurodegenerative disease that has no cure or disease modifying treatment. The development of effective treatments has been hindered by a lack of etiological knowledge, but gene replacement has emerged as a promising therapeutic platform for such disorders. Here, we utilize a mouse model of CLN3 disease to test the safety and efficacy of a cerebrospinal fluid-delivered AAV9 gene therapy with a study design optimized for translatability. In this model, postnatal day one administration of the gene therapy virus resulted in robust expression of human CLN3 throughout the CNS over the 24-month duration of the study. A range of histopathological and behavioral parameters were assayed, with the therapy consistently and persistently rescuing a number of hallmarks of disease while being safe and well-tolerated. Together, the results show great promise for translation of the therapy into the clinic, prompting the launch of a first-in-human clinical trial (NCT03770572).